Response of Summer Ozone to Precursor Emission Controls in the Yangtze River Delta Region - Mao, Yu-Hao; Yu, Shukun; Shang, Yongjie; Liao, Hong; Li, Nan (Frontiers in Environmental Science, 2022)
Surface ozone concentrations in the Yangtze River Delta (YRD) region in China have shown a significant increase with the dramatic reduction of anthropogenic nitrogen oxide (NOx) emissions since 2013. As the nonlinearity between ozone and its precursors (i.e., NOx and volatile organic compounds (VOCs)) varies greatly in time and space, we quantify the monthly changes of surface ozone with the co-control of NOx and VOCs anthropogenic emissions in the YRD region from May to October 2017 by using the GEOS-Chem model. Model evaluations show that the GEOS-Chem model exhibits good performance to simulate ozone concentrations in the region. For May–September 2017, most areas in the YRD region are under a transitional regime, but the regions with high anthropogenic emissions including Shanghai and southern Jiangsu are under a VOCs-limited regime. In October, basically, the entire YRD region is under a VOCs-limited regime. Generally, reducing VOCs emissions only is the most effective method for ozone control in the YRD. Nanjing is under a VOCs-limited regime in May, June, September, and October, and under a transition regime from July to August. The VOCs/NOx emission reduction ratio of 1:1 is effective for ozone mitigation in Nanjing (Shanghai) in May, June, and September (for May–September); the corresponding ratio is 2:1 in October. Hangzhou belongs to a transitional regime from May to September and is under a VOCs-limited regime in October. Reducing NOx emissions only would control ozone in Hangzhou from May to September, while the VOCs/NOx emission reduction ratio of 1:1 is favorable to reduce ozone concentrations in October. During high pollution days on July 22–27, 2017, the three cities belong to a transitional regime and reducing NOx emissions only is generally the most effective way to control high ozone pollution. GEOS-Chem tagged ozone simulation shows that ozone problem in the region is caused by the joint effect of local generation and regional and long-distance transport. Local generation (19.0–50.7%) is generally the largest contributor to monthly mean ozone concentrations in Jiangsu and Shanghai, Zhejiang, and central eastern China; the contribution of ozone from regions outside the YRD is larger in spring and autumn (42–76.0%) than in summer (23.3–51.8%). Since the annual VOCs (NOx) anthropogenic emissions in the region have shown a decline by 8% (11%) from 2017 to 2020 and would continue to reduce by 10% (10%) by 2025 according to the Chinese government requirement, the growth of ozone would be stopped in the YRD for May–September but likely to continue in October. Our study thus would provide a scientific base for guiding the effective emission reduction strategies to control ozone pollution in the YRD region.